Congenital erythropoietic porphyria with erythrodontia: A case report. Issue 4 (27th February 2019) - Ciftci, Volkan; Kılavuz, Sebile; Bulut, Fatma Derya; Mungan, Halise Neslihan; Bisgin, Atil; Dogan, Muharrem Cem
Abstract : Background: The causes for intrinsic tooth discoloration can be separated into two categories as systemic and local. Systemic causes are either genetic or drug‐induced effects. The development of dentition can also be affected by a number of systemic factors and metabolic diseases such as porphyria. Congenital erythropoietic porphyria (CEP), also known as Gunther's disease, is a metabolic disease caused by a transformation in the gene that codifies uroporphyrinogen‐3 synthesis, leading to porphyrin aggregation in urine, skin, bone, and dentin. Case Report: A 21‐month‐old girl with erythrodontia was referred to Paediatric Dentistry Department in September 2017. A physical examination revealed blisters on her face, nose, hands, and feet. Laboratory findings showed highly elevated urine total uroporphyrin and total coproporphyrin I and III levels. Next‐generation sequencing multigene panel testing for porphyria demonstrated a homozygous c.10C>T (p.L4F) mutation in the UROS gene. For curative therapy, the patient was admitted to the allogeneic bone marrow transplantation program. Conclusion: Congenital erythropoietic porphyria most commonly presents in the first few years of life. Manifestations can include reddish‐colored urine, skin blistering, scarring, and erythrodontia. A timely diagnosis can prevent undesirable skin findings of the disease and death due to hematological involvement before a curative allogeneic bone marrow transplantation is performed.